Cuando aún no existían los sueños - Czernecki, Stefan; Rhodes, Timothy (Artes de México, 2005)
How did humans begin to dream? This children's book from Mexico offers an interesting explanation involving a monstrous black butterfly, jungle animals and a quick-witted shaman who knows all the best spells